Disease-free survival of 15 years after primary surgery in a patient with advanced high-grade serous ovarian cancer: a case report and literature review - Shi, Yaoqi; Zhu, Shuaiying; Shan, Jiangjing; Xu, Yuhong (Frontiers in Oncology, 2025)
BackgroundOvarian cancer, particularly high-grade serous ovarian cancer (HGSOC), is the most lethal gynecological tumor, with most patients experiencing recurrence within 5 years. Long-term survival in HGSOC patients with advanced stages is exceedingly rare.Case summaryWe report a case of advanced HGSOC with exceptional long-term recurrence-free survival following initial treatment. In June 2009, the patient underwent suboptimal cytoreductive surgery for stage IIIC ovarian cancer, including total hysterectomy, bilateral salpingo-oophorectomy, omentectomy, appendectomy, and resection of mesenteric and peritoneal lesions. Postoperatively, residual lesions were observed in the mesenteries and para-aortic lymph nodes. Despite unfavorable prognostic factors (advanced stage, aggressive pathology, and incomplete resection), the patient showed remarkable chemosensitivity, remaining recurrence-free for 15 years.ConclusionThe factors influencing long-term survival in HGSOC patients are not yet fully understood. We present this rare case to contribute data for further studies on long-term survival in advanced HGSOC.